Antiviral treatment for hepatitis B virus recurrence following liver transplantation. (4th October 2013) - Lee, Sanghoon; Kwon, Choon Hyuck D.; Moon, Hyung Hwan; Kim, Tae‐Seok; Roh, Youngnam; Song, Sanghyun; Shin, Milljae; Kim, Jong Man; Park, Jae Berm; Kim, Sung Joo; Joh, Jae‐Won; Lee, Suk‐Koo
Abstract: The purpose of this study was to identify the factors associated with the recurrence of hepatitis B virus (HBV) following liver transplantation (LT) for HBV‐related disease and to recognize the outcome of treatment for HBV recurrence with oral nucleos(t)ide analogues. Six hundred and sixty‐seven LTs were performed for HBsAg‐positive adult patients in our institute from 1996 to 2010. HBV prophylaxis was performed by hepatitis B immunoglobulin (HBIG) monotherapy or HBIG and entecavir combination therapy. There were 63 cases (11.4%) of HBV recurrences during a median follow‐up of 51 months. The median time to HBV recurrence was 22 months. A preoperative HBV DNA load of more than 10 5 IU/mL, HBIG monotherapy, and hepatocellular carcinoma in the explant liver were independent risk factors for HBV recurrence following LT in multivariate analysis. Patient survival at 10 yr was 54.2% for HBV‐recurrent patients. Among patients with HBV recurrence, HBsAg seroclearance was achieved in 13 patients (20.6%), but HBsAg seroclearance did not affect survival in these patients after the recurrence of HBV (p = 0.28). The recurrence of HBV led to graft failure in six cases. HBV recurrence should be prevented by strict management of pre‐transplant HBV viremia and an effective post‐transplant HBV prophylaxis.